2016
DOI: 10.1371/journal.pone.0163988
|View full text |Cite
|
Sign up to set email alerts
|

LDL-Cholesterol Increases the Transcytosis of Molecules through Endothelial Monolayers

Abstract: Cholesterol has been identified as a causative factor in numerous pathologies including atherosclerosis and cancer. One of the frequent effects of elevated cholesterol levels in humans is the compromise of endothelial function due to activation of pro-inflammatory signalling pathways. While the mechanisms involved in endothelial activation by cholesterol during an inflammatory response are well established, less is known about the mechanisms by which cholesterol may affect endothelial barrier function, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Regarding adherens junctions, reduced VEcadherin/β-catenin expression in dilated cardiomyopathy was associated with endothelial cell degeneration, 60 whereas in post-ischaemic MO, Src inhibition prevented VEGF-mediated disruption of Flk/VE-cadherin/β-catenin complex and attenuated post-ischaemic MO, fibrosis and mortality. 61 In addition, key risk factors for HF development and progression have been shown experimentally to promote endothelial hyperpermeability by disrupting EIJ, namely, renin-angiotensin-aldosterone system activation, 62 inflammation, 63,64 hypoxia, 65 cardioplegic arrest, 66 hyperglycaemia, 67 oxidative stress, 68 increased circulating LDL 69,70 and free fatty acid 71 levels.…”
Section: Interendothelial Junctionsmentioning
confidence: 99%
“…Regarding adherens junctions, reduced VEcadherin/β-catenin expression in dilated cardiomyopathy was associated with endothelial cell degeneration, 60 whereas in post-ischaemic MO, Src inhibition prevented VEGF-mediated disruption of Flk/VE-cadherin/β-catenin complex and attenuated post-ischaemic MO, fibrosis and mortality. 61 In addition, key risk factors for HF development and progression have been shown experimentally to promote endothelial hyperpermeability by disrupting EIJ, namely, renin-angiotensin-aldosterone system activation, 62 inflammation, 63,64 hypoxia, 65 cardioplegic arrest, 66 hyperglycaemia, 67 oxidative stress, 68 increased circulating LDL 69,70 and free fatty acid 71 levels.…”
Section: Interendothelial Junctionsmentioning
confidence: 99%
“…At indicated time points (0, 2, 4, 6, 8 hr), the TEER was measured by using Millicell-ERS (Millipore, Germany) as previously described [31][32][33]. The TEER were detected and compared as the percent change from corresponding baseline values.…”
Section: Transendothelial Electrical Resistance (Teer) 2 X 10mentioning
confidence: 99%
“…The evaluation of G. kola ethanolic extract activity on LDL-uptake revealed a significant decrease in LDL uptake by endothelial cells stimulated with LPS and treated with the ethanolic extract at the concentrations of 50 and 100 µg/ml. Some studies using an in vitro permeability system and blocking LDL binding to LDL-receptors using an anti-LDL receptor antibody, revealed that LDL was responsible for an increase of the permeability of endothelial cells in an LDL-receptor-dependent manner (Magalhaes et al, 2016) 27 . The ethanolic extract of G. kola would therefore act by inhibiting specific LDL-receptors.…”
Section: -Discussionmentioning
confidence: 99%